Life on the brink: social stress, trauma and psychopathology: 29th European College of Neuropsychopharmacology Congress materials review - Frankova, Iryna (Psychosomatic Medicine and General Practice, 2017)
Background. Lifetime most people inevitably will be faced with stress. Life adverse events represent a major risk factor for mental disorders. The stress response promotes adaptive plasticity, or can become maladaptive and harmful, when the response is dysregulated, it depends on susceptibility. Thus, stress-related disorders become a real challenge in the development of treatment strategies. Methods. This review is based on materials of the 29th European college of neuropsychopharmacology congress (September 2016, Vienna), the participants of the “Eastern European Academy of the World Psychiatric Association” and "Servier" company specifically for psychiatric journals of WPA Zone 10 (East European Educational WPA-Servier Academy-“EEE WPA-Servier Academy”. The review will present materials from several symposiums: “Life on the brink: stress and psychopathology”, “Novel strategies towards targeted interventions in PTSD”. Results. As result, we anticipate that this review will promote knowledge about high quality standards of treatment and evidence-based researches regarding stress-related disorders and distribute them among the modern community of mental health experts. Conclusion. The stress impact occurs in multiple dimensions simultaneously. Understanding the interaction between stress, the brain and social behavior pave the way to the development of future treatment strategies. In addition, intervention can have different windows of opportunity, the same intervention can heal or harm, depending on the time of appointment.